Pengenalan Perangkat Komputer Dasar sebagai Upaya Meningkatkan Pengetahuan Siswa SDI Waioti Maumere: Introduction to Basic Computer Devices as an Effort to Increase the Knowledge of SDI Waioti Maumere Students - Darkel, Yohanes Brekmans M.; Koten, Yosafat Pati Koten; Rozady, Margaretha Paulina Novianty; Mado, Theresia Wihelmina; Bada, Claudia Betruchy; Lodan, Maria Wilhelmina; Muda, Henderikus Basilius Nong (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
In today's digital era, basic computer and Microsoft literacy training is very important, both for elementary school students and professional workers. Increasing use is recognized by several sectors, including the banking industry and the education sector. To overcome this, basic computer introduction activities were carried out in the context of outreach to the community, especially elementary school students. From the information found at the SDI Waioti Maumere Elementary School, some students are not yet familiar with current computer technology. So the service carried out aims to provide an introduction to basic computers to elementary school students at SDI Waioti Maumere, including an introduction to computer hardware and an understanding of using Microsoft Word as an effort to improve each student's ability to adapt to today's global world. The three steps in this activity process are preparation, implementation, and assessment. In this activity, the committee succeeded in initiating basic computer and Microsoft Word learning for 36 students divided into two classes, namely A and B.